11β-HSD Types 1 and 2 in the Songbird Brain - Rensel, Michelle A.; Ding, Jessica A.; Pradhan, Devaleena S.; Schlinger, Barney A. (Frontiers in Endocrinology, 2018)
Glucocorticoid (GC) hormones act on the brain to regulate diverse functions, from behavior and homeostasis to the activity of the hypothalamic-pituitary-adrenal (HPA) axis. Local regeneration and metabolism of GCs can occur in target tissues through the actions of the 11β−hydroxysteroid dehydrogenases (11β−HSD1 and 11β−HSD2, respectively) to regulate access to GC receptors. Songbirds have become especially important model organisms for studies of stress hormone action; however there has been little focus on neural GC metabolism. Therefore, we tested the hypothesis that 11β−HSD1 and 11β−HSD2 are expressed in GC-sensitive regions of the songbird brain. Localization of 11β−HSD expression in these regions could provide precise temporal and spatial control over GC actions. We quantified GC sensitivity in zebra finch (Taeniopygia guttata) brain by measuring glucocorticoid (GR) and mineralocorticoid (MR) receptor expression across six regions, followed by quantification of 11β−HSD1 and 11β−HSD2 expression. We detected GR, MR and 11β−HSD2 mRNA expression throughout the adult brain. Whereas 11β−HSD1 expression was undetectable in the adult brain, we detected low levels of expression in the brain of developing finches. Across several adult brain regions, expression of 11β−HSD2 co-varied with GR and MR, with the exception of the cerebellum and hippocampus. It is possible that receptors in these latter two regions require direct access to systemic GC levels. Overall, these results suggest that 11β−HSD2 expression protects the adult songbird brain by rapid metabolism of GCs in a context and brain region-specific manner.